2019
DOI: 10.1177/1049732319860265
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Expectations in Health Care Settings: Experiences of Transgender and Gender Diverse Adults in the Central Great Plains

Abstract: Transgender and gender diverse (TGD) individuals face a long-term, multifaceted process if they choose to begin a gender affirmation journey. Decisions to go on hormone therapy and/or have a surgical procedure necessitate the TGD individual to set up an appointment with a health care provider. However, when TGD patients interact with health care practitioners, problems can arise. This article documents and categorizes the types of unmet expectations that are common in the TGD patient–health care provider socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 42 publications
(65 reference statements)
1
60
0
Order By: Relevance
“…Health care encounters are also populated by stories of SGMs being treated like specimens (Meyer et al 2020) and extensive gatekeeping (Shuster 2016). When these situations happen, individuals report feeling caught off guard, embarrassed, or harassed (Meyer et al 2020) and less likely to use preventive care (Willging et al 2019).…”
Section: Health Carementioning
confidence: 99%
See 2 more Smart Citations
“…Health care encounters are also populated by stories of SGMs being treated like specimens (Meyer et al 2020) and extensive gatekeeping (Shuster 2016). When these situations happen, individuals report feeling caught off guard, embarrassed, or harassed (Meyer et al 2020) and less likely to use preventive care (Willging et al 2019).…”
Section: Health Carementioning
confidence: 99%
“…Furthermore, SGMs have also reported that they are met with paternalism and suspicion because of bias held by providers (Baker and Beagan 2014; Meyer et al 2020; Shuster 2019). For example, Shuster (2019) documented how providers of trans medicine say they used informed consent in their work with trans patients, but how they described their practices had little resemblance to an informed consent model.…”
Section: Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…This conceptual model is intended to educate students and professionals and may be useful as part of medical education curricula and health care protocols, especially for girls and young women experiencing CSE who present in emergency and reproductive health care settings. By reshaping the power structure and offering more control for youth seeking services, this model may serve as an initial and critical shift toward addressing pervasive unmet expectations and health care discrimination among diverse groups (Kattari & Hasche, 2016;Meyer et al, 2020). In addition, greater collaboration across sectors and disciplines, as well as partnering with survivors and survivor serving programs can ensure girls and young women affected by CSE are connected to services that meet their complex needs holistically, especially medical needs.…”
Section: Implications For Practicementioning
confidence: 99%
“…Qualitative research offers an important opportunity to elucidate the health and social experiences of populations and communities that are historically oppressed and repressed including but not limited to children, older adults, individuals experiencing homelessness, people who use illicit substances, those experiencing intimate partner violence, racial and ethnic minorities, those living with chronic or mental illness, and sexual and gender minority populations (Butler et al, 2019), and those living in rural areas, who may lack access to resources and for whom these experiences may be exacerbated (Cristancho et al, 2008;Meyer et al, 2019;Pendse & Nugent, 2017). Systemic racism and structural inequities are well-recognized barriers to equitable inclusion of these populations that are historically underrepresented in biomedical research.…”
Section: Introductionmentioning
confidence: 99%